Efeito antinociceptivo da toxina TX3-3 isolada do veneno da aranha Phoneutria nigriventer em modelos animais de dor - Gerusa Duarte Dalmolin (2010)
Venom peptides have produced exceptional lead compouds for drug development to treat pain. In the present study, we examined the antinociceptive and motor effects of Tx3-3, a peptide toxin isolated from Phoneutria nigriventer venom, which inhibit high voltage-dependent calcium channels (VDCC), preferentially P/Q and R-type VDCC. First, we tested the effects of Tx3-3 on nociceptive (tail-flick test), neuropathic (partial sciatic nerve ligation and STZ-induced diabetic neuropathy) and inflammatory (intraplantar Complete Freund's Adjuvant - CFA) animal models of pain. Additionally, we also tested the effect of Tx3-3 on morphine antinociception in opioid-tolerant and neuropathic mice. In the tail-flick test, both intrathecal (i.t.) and intracerebroventricular (i.c.v.) injection of Tx3-3 caused a short-lasting antinociceptive effect in mice, without impair motor functions, at least in doses that were 10-30 time higher than the effective dose. By comparison, -conotoxin MVIIC, a P/Q and N-type VDCC blocker derived from Conus magus venom, caused significant motor impairment at doses close to the efficacious dose in tail-flick test. Tx3-3 caused a long-lasting antinociceptive effect in neuropathic pain models. Intrathecal injection of Tx3-3 (30 pmol/site) decreased both mechanical allodynia produced by sciatic nerve injury in mice and STZ-induced allodynia in mice and rats. On the other hand, i.t. injection of Tx3-3 did not alter inflammatory pain. Furthermore, the i.t. injection of Tx3-3 before morphine challenge reestablished the morphine effectiveness in opioid-tolerant mice and allowed morphine antinociception in neuropathic mice. Taken together, our data show that Tx3-3 presentes good antinociceptive activity in neuropathic pain models and enables morphine-induced antinociception in opioid-tolerant and neuropathic hyperalgesic states. These findings suggest that Tx3-3 may be of interest in the management of pain states refractory to opioids.